A Conceptual Mapping of Communication Demands in Collaborative Software Development: Implications for the Inclusion of Developers with ADHD - Cartagena, Tatiana; Goelzer, Natalya; Velloso, Gabriel; Sousa, Andrêus; Beria, Francielle; Kohl, Karina; Marczak, Sabrina; Gama, Kiev (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2026: Anais do XXI Simpósio Brasileiro de Sistemas Colaborativos, 2026)
Communication is central to collaborative software development, enabling coordination and shared understanding. However, cognitive differences may affect how these interactions are experienced. This study investigates cognitive barriers in collaborative communication involving developers with ADHD. We adopt a qualitative and exploratory approach integrating Software Engineering and Psychology. Based on Grounding in Communication and Brown’s Executive Functions model, we propose a conceptual mapping relating communication situations to cognitive demands. Results highlight recurring demands on attention, working memory, and concurrent stimuli, illustrated through interviews with developers with ADHD.